2019
DOI: 10.1016/j.aim.2019.04.024
|View full text |Cite
|
Sign up to set email alerts
|

Mixed type Hermite-Padé approximation inspired by the Degasperis-Procesi equation

Abstract: In this work we present new results on the convergence of diagonal sequences of certain mixed type Hermite-Padé approximants of a Nikishin system. The study is motivated by a mixed Hermite-Padé approximation scheme used in the construction of solutions of a Degasperis-Procesi peakon problem and germane to the analysis of the inverse spectral problem for the discrete cubic string.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 27 publications
0
16
0
Order By: Relevance
“…The definition of a Nikishin system can be extended to the case when the intervals ∆ j are unbounded or touching. The results of this section remain valid when the Nikishin systems are constructed following the more general definition given in [13]. However, the asymptotic results given in Sections 3-4 require that we use the more restricted version presented here (which, incidentally, coincides with its original formulation in [15]).…”
Section: Multi-orthogonality Relationsmentioning
confidence: 75%
See 2 more Smart Citations
“…The definition of a Nikishin system can be extended to the case when the intervals ∆ j are unbounded or touching. The results of this section remain valid when the Nikishin systems are constructed following the more general definition given in [13]. However, the asymptotic results given in Sections 3-4 require that we use the more restricted version presented here (which, incidentally, coincides with its original formulation in [15]).…”
Section: Multi-orthogonality Relationsmentioning
confidence: 75%
“…, m, is obtained solving a homogeneous linear system of (n + 1)m equations on the (n + 1)m + 1 coefficients of the polynomials. Among other properties, in [13] (see also Lemma 2.4 below) it was shown that deg a n,m = n and the vector of polynomials (a n,0 , . .…”
Section: )mentioning
confidence: 99%
See 1 more Smart Citation
“…Such areas cover, but are not limited to, number theory, non-intersecting brownian motions, multiple orthogonal polynomial ensembles, random matrix theory, and differential equations. For specific references see [12]. In particular, in [13] they were used to find discrete (peakon) solutions of the Degasperis-Procesi partial differential equation (see also references therein).…”
Section: Introductionmentioning
confidence: 99%
“…We wish to point out that the pair of measures appearing in the problem form a generator of a Nikishin system (see definition in next subsection). For more details see [13] and [12,Appendix].…”
Section: Introductionmentioning
confidence: 99%